Supporting the mental health needs of veterans in the metro Detroit area - Tanielian, Terri L. (RAND Corporation, 2016)
Supporting the mental health needs of veterans is a national priority. Over the past decade, there have been several studies describing the needs of the veteran population, particularly those who served in the post-9/11 era, calling for improved access to high-quality mental health services. In response, the federal government has expanded funding and services to meet increasing demand. At the same time, there has also been a proliferation of nongovernmental support to improve services for veterans in local communities. Often, in an attempt to deploy resources quickly, new programs and services are implemented without a full understanding of the specific needs of the population. This report discusses findings and recommendations from a study designed to gather information on the mental health- elated needs facing veterans in the Detroit metropolitan area to identify gaps in the support landscape and inform future investments for community-level resources to fill the identified gaps.